The Rise and Fall of the Great Powers : Economic Change and Military Conflict from 1500 to 2000 - Kennedy,Paul (Lahore Services Book Club, 1991)
Examines the relationship of economic to military power as it affects the rise and fall of empires.
Include Bibliography Index
Keywords: The Rise and Fall of the Great Powers : Economic Change and Military Conflict from 1500 to 2000 -- History, Modern -- Balance of power